Principal Leadership in Improving the Quality of Education through School based Management at SMP Negeri 4 Takengon - Sarmini Sarmini; Siraj Siraj; Suparta Rasyid (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study was to analyze the planning, implementation, and evaluation of the application of School-Based Management on the quality of education. This study used a qualitative research method with a descriptive approach. Data were collected through interviews, observations, and documentation. Data analysis was carried out qualitatively using thematic analysis techniques. The results of the study showed (1) The process of managing School-Based Management begins with planning. This is part of the process of planning actions to be taken to achieve the goals of the school program. (2) To improve the quality of education, all parts of society and government must work together. (3) To find out how effective and successful the school program is, the school-based management evaluation process is very important. The results of the evaluation are used by schools to determine the strengths and weaknesses of the program for improvement in the following year.